Arylsulfonamido-alkyl-sulfamates act as inhibitors of bovine carbonic anhydrase II - Toni C. Denner; Niels V. Heise; René Csuk (European Journal of Medicinal Chemistry Reports)
A small library of arylsulfonamido-alkyl sulfamates was prepared by a two-step synthesis from readily available starting materials. The compounds were tested for their ability to inhibit bovine carbonic anhydrase II. Several of them were found as good competitive inhibitors holding Ki values as low as Ki = 0.9 μM (compound 47b). The activity was influenced by the substitution pattern of the arylsulfonamide moiety as well as the length of the spacer to the distal sulfamate group. Molecular docking studies were used to substantiate these findings. For the aryl-substituted analogues, the increase in inhibitory activity for compounds with a shorter spacer can be explained by stabilization via aromatic π-interactions. For the cyclopropyl or methylsulfonyl substituted analogues, their inhibitory activity can be attributed to their reduced steric hindrance. These results provide a basis for designing effective CA II inhibitors.